Obesity and labor market outcomes - Susan L. Averett (IZA World of Labor, 2014)
Rising obesity is not only a pressing global public health problem. There is also substantial evidence that obese people, particularly women, are less likely to be employed and, when employed, are likely to earn lower wages. There is some evidence that the lower earnings are a result of discriminatory hiring and sorting into jobs with less customer contact. Understanding whether obesity is associated with adverse labor market outcomes and ascertaining the source of these outcomes are essential for designing effective public policy.
Keywords: J7; J78; J71; 330; obesity; BMI; wages; employment; occupation; absenteeism